May the brief physical activity assessment tool accurately measure physical activity in patients with resistant hypertension?. (29th July 2021) - Lopes, S; Mesquita-Bastos, J; Garcia, C; Figueiredo, D; Carvalho, P; Oliveira, J; Polonia, J; Alves, AJ; Ribeiro, F
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): FEDER Funds through the Operational Competitiveness Factors Program—COMPETE National Funds through the Portuguese Foundation for Science and Technology (FCT) "PTDC/DTP-DES/1725/2014". SL is a PhD fellow supported by the FCT (Grant Ref: SFRH/BD/129454/2017). Introduction: Resistant hypertension is a major health problem due to the increased risk of cardiovascular events and mortality. Physical activity and exercise reduces blood pressure in resistant hypertension and is associated with lower cardiovascular risk and mortality. It is presently recommended that physical activity assessment should be a priority in all visits to health settings Purpose: This study aims to determine if the Brief Physical Activity Assessment Tool (BPAAT), a 2-question tool to assess physical activity, is a valid instrument to detect inactive patients with resistant hypertension.  Methods: Sixty patients with a diagnosis of resistant hypertension were recruited. Outcome measures included clinical data, blood pressure and daily physical activity. Physical activity was objectively measured over a 7-day period with an accelerometer and subjectively assessed (self-assessment) by the BPAAT. The association between the BPAAT and accelerometry, according to the BPAAT scoring categories, was assessed bythe percentage of agreement, Cohen's Kappa and sensitivity and specificity. Results: Patients (33 were male) had a mean age of 59.4 ± 9.1years, were on average overweight (BMI 29.5 ± 4.5 kg/m2) and on an average of 4.5 ± 0.7 antihypertensive medications. Forty-two patients (70%) were classified as insufficiently active by the BPAAT compared to the 38 (63.3%) insufficiently active patients identified by the accelerometry data. Regarding the questionnaire's specificity and sensitivity, the BPAAT correctly identified 32 [84.2 (73.1 – 95.3) %] of the 38 'insufficiently active' patients and 12 [54.5 (34.3 – 74.7) %] of the 22 'sufficiently active' patients identified by accelerometry. The agreement between BPAAT and accelerometry to identify sufficiently/insufficiently active patients, according to the BPAAT's cut-off values was fair to moderate (Kappa = 0.403 (0.162 – 0.674), with a percentage of agreement of 73.3%. Conclusion: The BPAAT, a 2-question tool to assess physical activity, seems to be a valid and fast solution to identify insufficiently active adults with resistant hypertension during routine clinical visits.